Sociological Explanation of Resilience and Self-Control Effect on the Law-Aversion of Citizens (The Study: Ilam Province) - siavash khodayari; Esmaeil Jahanbakhsh (توسعه اجتماعی)
This study aimed to investigate the effect of self-control and resiliency over the law-avasion between the citizens of Ilam. Law-aversion (soft) in both dimension subjective and objective studied. The method of this survey is survey, and the kind of correlation is the questionnaire. The statistical population consists of all citizens over 18 years of ilam province in 2016; and sampling type, multi - stage cluster and sample size were estimated based on the Morgan table. The findings and results of this study showned that self-control and resilience variables additive effect, positive and direct the on citizens of Ilam province is lawl-aversion. The results of the test structural equation modeling (Amos) shows the resiliency 0/23 Explanations of variances in the community, and self-control variable 0/30 the variance of the dependent variable (law-aversion) predicts in the community.. With regard to the findings, empowerment and entrepreneurial spirit and self-control are essential twisting.